2016
DOI: 10.3109/21691401.2016.1138488
|View full text |Cite
|
Sign up to set email alerts
|

Polymerization of modified diaspirin cross-linked hemoglobin (DCLHb) with 1,6-bismaleimic-hexane

Abstract: Increasing the size of hemoglobin (Hb) by polymerization offers the benefits of reduced renal clearance and increased duration in the vascular circulation. With this goal, diaspirin cross-linked hemoglobin (DCLHb) was modified in order to keep one thiol group on the surface and then polymerized with 1,6-bismaleimic-hexane (1,6-BMH) to increase the molecular weight. The HPLC results indicated that approximate 20% dimers to tetramers of DCLHb desired were achieved after the polymerization. It was also demonstrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…It is suggested that aggregation of WP may be improved by ALM pectin after a lag period. Similarly, Qi et al (2016) found that free sulphydryl groups of WP was mitigated by conjugating with sugar beet pectin.…”
Section: Effects Of Alm Pectin On Free Sulfhydryl Groups Of Polymerizmentioning
confidence: 90%
See 1 more Smart Citation
“…It is suggested that aggregation of WP may be improved by ALM pectin after a lag period. Similarly, Qi et al (2016) found that free sulphydryl groups of WP was mitigated by conjugating with sugar beet pectin.…”
Section: Effects Of Alm Pectin On Free Sulfhydryl Groups Of Polymerizmentioning
confidence: 90%
“…β-Lactoglobulin has two intramolecular disulphide bonds and one embedded free sulohydryl group while α-lactalbumin has four intramolecular disulphide bonds and no thiol group (Qi, Wang, Chen, Guo, & Wang, 2016). WP aggregates mainly by forming intermolecular disulphide bonds (Kehoe, Wang, Morris, & Brodkorb, 2011).…”
Section: Effects Of Alm Pectin On Free Sulfhydryl Groups Of Polymerizmentioning
confidence: 99%